2019
DOI: 10.4149/bll_2019_046
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 and caspase-cleaved cytokeratin-18: Promising biomarkers for Alzheimer’s disease?

Abstract: OBJECTIVES: To investigate the use of nesfatin-1 and caspase-cleaved cytokeratin-18 serum levels as biomarkers in Alzheimer's disease. METHODS: The study group consisted of 39 patients with Alzheimer's disease (AD) and 39 controls. Demographic characteristics including gender, age, body mass index, mini-mental status examination (MMSE) and duration of disease were recorded. The ELISA method was used to measure serum nesfatin-1 and CCCK-18 levels in serum samples. RESULTS: Serum nesfatin-1 levels were statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Chen et al, 2019; Ge et al, 2015). Higher plasma level of nesfatin-1 was also reported in AD or diabetes mellitus patients and animal models (Alpua & Kisa, 2019) (Dong et al, 2013), with significant correlation to the cognitive dysfunction. In the present study, our results showed that the serum nesfatin-1 concentration was increased in the bilaterally hippocampal STZ-injected mice.Although the mechanism remains unclear, this results provide new evidence that nesfatin-1 might be involved with the insulin metabolism disorder-associated cognitive impairment in AD.…”
Section: Discussionmentioning
confidence: 81%
“…Chen et al, 2019; Ge et al, 2015). Higher plasma level of nesfatin-1 was also reported in AD or diabetes mellitus patients and animal models (Alpua & Kisa, 2019) (Dong et al, 2013), with significant correlation to the cognitive dysfunction. In the present study, our results showed that the serum nesfatin-1 concentration was increased in the bilaterally hippocampal STZ-injected mice.Although the mechanism remains unclear, this results provide new evidence that nesfatin-1 might be involved with the insulin metabolism disorder-associated cognitive impairment in AD.…”
Section: Discussionmentioning
confidence: 81%
“…Results of our previous study demonstrated that peripheral abundance of nesfatin-1 could be changed by high-fat diet and chronic stress, and ip injection of nesfatin-1 could induce anxiety and depressionlike behavioral disorder in rats, together with the change of hippocampal synaptic plasticity (Ge et al, 2015;Chen et al, 2019). Higher plasma level of nesfatin-1 was also reported in AD or diabetes mellitus patients and animal models (Dong et al, 2013;Alpua and Kisa, 2019), with significant correlation to the cognitive dysfunction. In the present study, our results showed that the serum nesfatin-1 concentration was increased in the bilaterally hippocampal STZ-injected mice.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, little is known about the role of KRT18 in VD. However, according to a recent study (Alpua and Kisa 2019), caspase-cleaved keratin 18 (CCCK-18) can be used as a prognostic biomarker for Alzheimer's disease. Further comprehensive studies should be performed to clarify the use of CCCK-18 levels as a biomarker for other neuronal diseases.…”
Section: Discussionmentioning
confidence: 99%